2015
DOI: 10.3109/02699206.2015.1102970
|View full text |Cite
|
Sign up to set email alerts
|

Processing complex pseudo-words in mild cognitive impairment: The interaction of preserved morphological rule knowledge with compromised cognitive ability

Abstract: Mild cognitive impairment (MCI) affects the cognitive performance of elderly adults. However, the level of severity is not high enough to be diagnosed with dementia. Previous research reports subtle language impairments in individuals with MCI specifically in domains related to lexical meaning. The present study used both off-line (grammaticality judgment) and on-line (lexical decision) tasks to examine aspects of lexical processing and how they are affected by MCI. 21 healthy older adults and 23 individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 46 publications
2
5
0
1
Order By: Relevance
“…The other noteworthy result was the failure to find the expected pattern for response times and acceptance rates for the re- violation items. While all the other experiments using a similar affixation violation-type manipulation consistently find that grammatical category violations are rejected more robustly, and more quickly, than argument structure violations, in Greek (Manouilidou, 2007; Manouilidou and Stockall, 2014; Neophytou et al, 2018), English (Manouilidou and Stockall, 2014), and Slovenian (Manouilidou et al, 2016), no such effect is found for the re- prefixed items in the current experiment. This null effect is not a mere absence of a statistically significant effect attributable to noisy data (the SDs in the re- conditions were similar to those for the other prefixes), but the genuine absence of any hint of a difference between the two violation conditions in acceptance rate, and a trend to an opposite direction pattern in the response time.…”
Section: Discussionsupporting
confidence: 45%
“…The other noteworthy result was the failure to find the expected pattern for response times and acceptance rates for the re- violation items. While all the other experiments using a similar affixation violation-type manipulation consistently find that grammatical category violations are rejected more robustly, and more quickly, than argument structure violations, in Greek (Manouilidou, 2007; Manouilidou and Stockall, 2014; Neophytou et al, 2018), English (Manouilidou and Stockall, 2014), and Slovenian (Manouilidou et al, 2016), no such effect is found for the re- prefixed items in the current experiment. This null effect is not a mere absence of a statistically significant effect attributable to noisy data (the SDs in the re- conditions were similar to those for the other prefixes), but the genuine absence of any hint of a difference between the two violation conditions in acceptance rate, and a trend to an opposite direction pattern in the response time.…”
Section: Discussionsupporting
confidence: 45%
“…Weiner et al [5] have found a close correlation between the severity of dementia and different linguistic metrics; nevertheless, the results in studies with patients in the mild-tomoderate stages of AD [6,7] cannot be generalized to earlier stages of the disease when compensatory abilities may result in more subtle impairments in functional language [8]. However, specific studies involving people with MCI have identified subtle language deficits [9] in tasks involving the naming of images and semantic tests, which are usually reflected in problems finding the right word in a given situation [10], changes in the frequency of words used for more common words [11], temporal changes in spontaneous language [3] with deficits in verbal fluency tasks [12], and phonemic paraphasia due to the difficulty in producing speech sounds in the right order [13].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that language impairment occurs early and commonly in the progression of AD, motivated many researchers to identify markers of language impairment in MCI. For example, Manouilidou et al ( 31 ) showed that while MCI individuals preserve morphological rule knowledge, they face processing difficulties of pseudo-words (for a discussion and review of current studies, see 32 , 33 ). As there is only a handful of studies on the acoustic properties of MCI speech (e.g., 30 , 34 ), more research on speech acoustics is required to gain a better understanding of how MCI speech differs from that of healthy controls.…”
Section: Introductionmentioning
confidence: 99%